Proportionality Principle as a Response Instrument to Challenges of Modern Labour Law - Kardava, Ekaterine (Journal of Law, 2017)
Proportionality Principle is the fundamental principle of public and private laws and the basic regulatory instrument of modern relations measuring the use of power. Integration of the principle into the labour law in the form of systematized test (three-stage test) - is the subject of recent debates. The issue is actual caused by contradiction between the traditional approaches of the labour law and modern labour market challenges. The proportionality principle and the application of its structured test to labour relations’ debates is considered as one of the responsive mechanism to the challenging process. It is addressed in labour cases not only for the analyzing of employers but employees (mostly trade unions) actions, as well for final assessment and decision-making. The practice still is developing. It echoes the modern process within of which there are discussion on possibilities of modification of labour law doctrinal objectives. It implies changes of selective nature of the labour low towards the universal. The study on the practice of application of proportionality and its development within the national labour law of Georgia is the subject of utmost interest with regard to the fulfillment of the Association Agreement and transposition of European standards into the national legislations. Georgia should conduct the legal approximation activities in labour law field, which requires the complex and systemized vision: not only setting of compliance with EU directives, but cognition of the principles, which are the bases for interpretation of the AA norms and their use in practice.